Man on a mission. (Prospect, 2012)
The article focuses on the efforts of the government to tackle computer hacking in Great Britain. It offers information on Tom Watson, Member of Parliament (MP), who speaks against News International Ltd. and hacking in the parliament. It focuses on the close relationship between politicians and mass media. It offers information on the Press Complaints Commission that was one of the most damaged, brand in Great Britain.